Dynamic Spin-Fluctuation Theory of Metallic Magnetism - Melnikov, Nikolai B. (Springer International Publishing, 2018)
This book presents a theoretical framework for magnetism in ferromagnetic metals and alloys at finite temperatures. The objective of the book is twofold. First, it gives a detailed presentation of the dynamic spin-fluctuation theory that takes into account both local and long-wave spin fluctuations with any frequency. The authors provide a detailed explanation of the fundamental role of quantum spin fluctuations in the mechanism of metallic magnetism and illustrate the theory with concrete examples. The second objective of the book is to give an accurate and self-contained presentation of many-body techniques such as the functional integral method and Green's functions, via a number of worked examples. These computational methods are of great use to solid state physicists working in a range of specialties. The book is intended primarily for researchers, but can also be used as textbook. The introductory chapters offer clear and complete derivations of the fundamentals, which makes the presentation self-contained. The main text is followed by a number of well-organized appendices that contain a detailed presentation of the necessary many-body techniques and computational methods. The book also includes a list of symbols and detailed index. This volume will be of interest to a wide range of physicists interested in magnetism and solid state physics in general, both theoreticians and experimentalists.